Epilepsy with myoclonic‐atonic seizures (Doose syndrome): Clarification of diagnosis and treatment options through a large retrospective multicenter cohort. (14th November 2020) - Nickels, Katherine; Kossoff, Eric H.; Eschbach, Krista; Joshi, Charuta
Abstract: Objective: Epilepsy with myoclonic‐atonic seizures (EMAS) is a rare childhood onset epileptic encephalopathy. There is no clear consensus for recommended treatments, and pharmacoresistance is common. To better assess the clinical phenotype, most effective treatment, and determinants of cognitive and seizure outcomes, three major pediatric epilepsy centers combined data, creating the largest cohort of patients with EMAS ever studied to date. Methods: Authors performed a retrospective chart review of patients with EMAS who received care at the authors' institutions. Results: A total of 166 children were identified. Global developmental delay (>1 domain) was present in 2% of children at onset and 49% during the course of the disease. Afebrile seizures occurred after the age of 2 years in 88%, generalized tonic‐clonic seizures in 60%, and drop attack or myoclonic seizures in 30%. At onset, electroencephalography (EEG) found 28% normal, background slowing in 20%, and epileptiform discharges or seizures in 69%. Subsequent EEG found slowing in 62% and discharges or seizures in 90%. Response (>50% seizure reduction) to the first three antiseizure drugs (ASDs) was 26% (levetiracetam, 17%; valproic acid, 31%; other ASDs combined, 26%). Diet therapy was used as a second or third therapy in 19% and ultimately used in 57%; response was 79%, significantly greater than the first three ASDs ( P  = .005, χ 2 ). Seizure freedom occurred in 57% and was less likely in the case of persistent global developmental delays ( P  < .001), seizure recorded on subsequent EEGs ( P  = .027), and failure to respond to diet therapy ( P  = .005). Development was normal in 47%, and 12% had delays in one domain, which was less likely in the case of global developmental delay after epilepsy onset ( P  < .001) and failure to achieve seizure freedom ( P  < .001). Significance: This large cohort of children with EMAS clarifies areas of variability in practice. Diet therapy is by far the most effective treatment; failure to respond was associated with failure to attain seizure freedom. This therapy should be used early in the treatment in EMAS. This study also identified a bidirectional link between cognitive and seizure outcomes.